ISens: A Fiber‐Based, Highly Permeable and Imperceptible Sensor Design. Issue 37 (2nd August 2021) - Stockinger, Thomas; Wirthl, Daniela; Mao, Guoyong; Drack, Michael; Pruckner, Roland; Demchyshyn, Stepan; Steiner, Melanie; Egger, Florian; Müller, Uwe; Schwödiauer, Reinhard; Bauer, Siegfried; Arnold, Nikita; et al.
Abstract: Embedded sensors are key to optimizing processes and products; they collect data that allow time, energy, and materials to be saved, thereby reducing costs. After production, they remain in place and are used to monitor the long‐term structural health of buildings or aircraft. Fueled by climate change, sustainable construction materials such as wood and fiber composites are gaining importance. Current sensors are not optimized for use with these materials and often act as defects that cause catastrophic failures. Here, flexible, highly permeable, and imperceptible sensors (iSens) are introduced that integrate seamlessly into a component. Their porous substrates are readily infused with adhesives and withstand harsh conditions. In situ resistive temperature measurements and capacitive sensing allows monitoring of adhesives curing as used in wooden structures and fiber composites. The devices also act as heating elements to reduce the hardening time of the glue. Results are analyzed using numerical simulations and theoretical analysis. The suggested iSens technology is widely applicable and represents a step towards realizing the Internet of Things for construction materials. Abstract : Permeable sensors fabricated of paper or glass fibers for measuring the temperature and monitoring the curing of adhesives during production are fabricated. The paper substrate fits seamlessly into the wooden construction material, while in the case of composite materials the glass fibers themselves are electrically functionalized. This technology ushers in a new generation of imperceptible sensors (iSens) and devices.